Public Spending - McKean, Roland N. (New York McGraw-Hill, 1968)
The aim of this book is to help students and other readers understand how public-spending choices are made, what some of the consequences of various choices are, and what would be the effects of using certain instruments to influence those choices.
Includes index
osc 28/6/17
Loans
Keywords: Public expenditure